The metamorphosis - Kafka, Franz, 1883-1924.; Corngold, Stanley (Toronto ; New York, N.Y. : Bantam Books, 1986)
A novel about a man who finds himself transformed into a huge insect, and the effects of this change upon his life. This is a fantastic horror story about a hapless man who is turned into an insect. When Gregor Samsa woke up one morning from unsettling dreams, he found himself changed in his bed into a monstrous vermin. With this startling, bizarre, yet surprisingly funny first sentence, Kafka begins his masterpiece, The Metamorphosis. It is the story of a young man who, transformed overnight into a giant beetlelike insect, becomes an object of disgrace to his family, an outsider in his own home, a quintessentially alienated man. A harrowing -- though absurdly comic -- meditation on human feelings of inadequacy, guilt, and isolation, The Metamorphosis has taken its place as one of the most widely read and influential works of twentieth-century fiction.
Translation of: Die Verwandlung.
Contains letters by Kafka, diary entries and 10 critical essays.
Includes bibliographical references.
Keywords: Kafka, Franz, -- 1883-1924.; Kafka, Franz, -- 1883-1924 -- Criticism and interpretation; Metamorphosis -- Fiction; Psychological fiction; Black humor (Literature)